2012
DOI: 10.1155/2012/287309
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Epworth Sleepiness Scale Scores in a Rural Population

Abstract: High levels of sleepiness in this population were common. Obesity was an important risk factor for high ESS score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 65 publications
7
18
0
1
Order By: Relevance
“…Consistent with results from our pilot study (40), the present study highlights that a significant percentage of the rural population experienced symptoms of excessive daytime sleepiness. This finding has implications for potential increased risks for farm-related and other forms of accidents/injuries, as well as potential increased cardiovascular morbidity risk.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with results from our pilot study (40), the present study highlights that a significant percentage of the rural population experienced symptoms of excessive daytime sleepiness. This finding has implications for potential increased risks for farm-related and other forms of accidents/injuries, as well as potential increased cardiovascular morbidity risk.…”
Section: Discussionsupporting
confidence: 91%
“…The validity and reliability of the ESS has been evaluated (33,(36)(37)(38)(39). In an earlier pilot project, we studied the prevalence of a high ESS score in 283 rural residents (40). The objective of the present study was to broaden the evaluation of excessive daytime sleepiness prevalence and determinants in the much larger rural population participating in the Saskatchewan Rural Health Study (SRHS) (41).…”
Section: Une Somnolence Diurne Excessive Chez Des Habitants Des Régiomentioning
confidence: 99%
“…14 Excessive daytime sleepiness (defined by ESS > 10) was a concerning discovery in our sample, significantly higher than in healthcare professionals and in the rural general population, as previously studied. 15,16 Also, the incidence of severe excessive daytime sleepiness was higher than in the French study. 13 Regarding the perceived stress, we found PSS scores again significantly higher compared to those in a recent study in the Danish population (median of 11).…”
Section: Discussionmentioning
confidence: 62%
“…There was no difference in the percentage of patients with an ESS score > 10 in the CPAP group compared with the controls (16.1 versus 14.3, P = 0.54). In the most recent studies in the general population, Pahwa et al (2012) found that 21% of randomly selected individuals in a Canadian rural population had ESS scores > 10, while this prevalence of 10.9% was reported by Johns and Hocking (1997) in an Australian working population in 1997. Accordingly, in the Ohayon (2012) study, 19.5% of the randomly selected population reported severe excessive sleepiness, and 20% moderate excessive sleepiness, but the ESS was not used.…”
Section: Discussionmentioning
confidence: 96%